Exploring factors that influence success when introducing "The Safewards Model" to an acute adolescent ward: A qualitative study of staff perceptions. Issue 3 (25th January 2022) - Yates, Nicholas J.; Lathlean, Judith
Abstract: Problem: The Safewards' model identifies factors that can lead to conflict and addresses these factors, using ten interventions, within inpatient mental health wards aiming to reduce "conflict and containment." The Department of Health (2014) and Care Quality Commission (2017) supported the use of Safewards to reduce restrictive practice across all mental health settings in the UK, but its application to adolescent mental health remains relatively unexplored. This study therefore aims to address the research question: "What are the factors influencing the success of ten Safewards' interventions when implemented onto an acute adolescent ward?" Methods: Eight healthcare assistants and two nurses who had attended Safewards' training participated in semi‐structured interviews four months after Safewards was introduced to an acute adolescent ward. The interviews were transcribed verbatim and analyzed using thematic analysis. Data analysis was conducted inductively by developing data‐driven themes. Findings: Many of the factors influencing Safewards' success in adolescent mental health (e.g., acuity; dependence on nonregular staffing; lack of leadership and operating procedures) paralleled the evidence found in adult services. Conclusions: This study contributes new information by implementing "mutual help" and "calm down" principles with adolescents, as well as discussing barriers of operational procedures and benefits of patient involvement.